Implementation of the remote activities of the Programa Academia da Cidade in times of COVID-19 - Gledson da Silva Oliveira; Raquel Bezerra Pajeú; Emmanuelly Correia de Lemos; Rafael Miranda Tassitano; Renan Wallacy Yvson dos Santos; Charles Barbosa Gomes da Silva; Danyelle de Cássia Ribeiro de Oliveira; Tatiana Martins Ferraz Holmes; Luiz Eduardo Nunes de Souza; Marcílio Paulo da Silva; Gabriela Maranhão Câmara Campos; Ricardo Augusto Menezes da Silva (Revista Brasileira de Atividade Física e Saúde)
Due to the COVID-19 pandemic, the face-to-face interventions of the Academia da Cidade of Recife (PAC-REC) were suspended and a remote activity plan was elaborated. The aim of this study was to describe the implementation and results of remote PAC-REC activities during the COVID-19 pandemic. A quantitative and qualitative analysis was performed based on the PAC-REC online reports and the virtual platforms referring to the remote activities carried out, from April to July 2020. For the implementation of the remote activities, integrated and systematic planning and monitoring meetings among the professionals and the program management were made. The following material was produced: 14 livestreams of bodily practices and physical activities, 10 interviews, 70 videos with different themes, 85 infographics, among others specified by pole. It is concluded that the performance of remote activities of PAC-REC reached its objectives and some should be maintained after the return of face-to-face activities.